2012
DOI: 10.1186/1471-244x-12-73
|View full text |Cite
|
Sign up to set email alerts
|

Utility and limitations of PHQ-9 in a clinic specializing in psychiatric care

Abstract: BackgroundThe Patient Health Questionnaire-9 (PHQ-9), despite its excellent reliability and validity in primary care, has not been examined for administration to psychiatric patients. This study assesses the accuracy of PHQ-9 in screening for major depressive episode and in diagnosing major depressive episode in patients of a psychiatric specialty clinic.MethodsWe compared operational characteristics of PHQ-9 as a screening and diagnostic instrument to DSM-IV-TR diagnosis by a trained psychiatrist as a referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 13 publications
0
67
0
Order By: Relevance
“…High specificity (490%) was reached with a threshold of 10 or higher, but a high positive predictive value was not reached with any cut-off score. The salient implication is that PHQ-9 used in psychiatric specialties might be suitable for screening purposes with the threshold of 10 for MDD, but not for diagnostic purposes (Inoue et al, 2012). Previous studies in India, China and South Korea have shown that the sensitivity and specificity of the PHQ-9 ranged from 0.80 to 0.93, and from 0.75 to 0.86, respectively, at the cutoff point of 5 (Wang et al, 2014;Han et al, 2008;Poongothai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…High specificity (490%) was reached with a threshold of 10 or higher, but a high positive predictive value was not reached with any cut-off score. The salient implication is that PHQ-9 used in psychiatric specialties might be suitable for screening purposes with the threshold of 10 for MDD, but not for diagnostic purposes (Inoue et al, 2012). Previous studies in India, China and South Korea have shown that the sensitivity and specificity of the PHQ-9 ranged from 0.80 to 0.93, and from 0.75 to 0.86, respectively, at the cutoff point of 5 (Wang et al, 2014;Han et al, 2008;Poongothai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[5] PHQ-9 is a brief self-rating questionnaire that is known for its excellent feasibility, reliability, validity and sensitivity but lower specificity and positive predictive value. [21][22][23] Overall it has been shown to be a valid measure of depression in different cultures and translations. [24] The use of PHQ-9 in ataxia patients is complicated by the fact that one of the 9 items is related to slowness of movements and speech which may be due to ataxia rather than reflecting depressive mood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, major depressive was accounted for if the answer to item number 1 or 2 and four or more of the remaining PHQ-9 items recorded at least as "more than half the days". Based on these criteria, a PHQ-9 score of ≥10 was used as a diagnostic cutoff point for depressive symptoms as previously recommended in the literature [17,18].…”
Section: Description Of Phq-9 Instrumentmentioning
confidence: 99%